Potential role of stem cells in severe spinal cord injury: current perspectives and clinical data - Paspala SA (Dove Medical Press, 2012)
Syed AB Paspala,1,2 Sandeep K Vishwakarma,1 Tenneti VRK Murthy,2 Thiriveedi N Rao,2 Aleem A Khan11PAN Research Foundation, CARE, 2The Institute of Medical Sciences, Hyderabad, IndiaAbstract: Stem cell transplantation for spinal cord injury (SCI) along with new pharmacotherapy research offers the potential to restore function and ease the associated social and economic burden in the years ahead. Various sources of stem cells have been used in the treatment of SCI, but the most convincing results have been obtained with neural progenitor cells in preclinical models. Although the use of cell-based transplantation strategies for the repair of chronic SCI remains the long sought after holy grail, these approaches have been to date the most successful when applied in the subacute phase of injury. Application of cell-based strategies for the repair and regeneration of the chronically injured spinal cord will require a combinational strategy that may need to include approaches to overcome the effects of the glial scar, inhibitory molecules, and use of tissue engineering strategies to bridge the lesion. Nonetheless, cell transplantation strategies are promising, and it is anticipated that the Phase I clinical trials of some form of neural stem cell-based approach in SCI will commence very soon.Keywords: stem cell therapy, regeneration, spinal cord injury, cell dosing, cell tracking